TECHNOLOGIES ON THE FRONTIERS OF EDUCATION-RHIZOME - Zapala Rabelo, Claudio Renato (2025)
This article is a text/rhizome in dialogue with the networks of everyday know-how woven in two decades dedicated to the study of new media, trends and contemporary technologies of sociability. The problem that motivates us concerns the roles of education and communication in the face of challenges surrounding communication technologies. How to deal with the technological profusion that does not keep up with the slow pace of bodies and minds? The research that resulted in state and regional awards, in addition to expanding academic dialogues to exponential audiences, was carried out using the everyday method, focusing on understanding pedagogical possibilities that do not dichotomize the interconnections between physical spaces and digital interfaces. The historical contextualization of communication technologies and theories illustrates how it is possible to give new meaning to the means, resources, strategies and languages ​​at the intersections between education and new media.